Comparison of HPLC metabolite profile and antioxidant activity of aqueous extract of Ginkgo Biloba from Two commercial products available in Bangladesh market - Ahmed, Sarin (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2020.